2014
DOI: 10.1371/journal.pone.0081229
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis Reveals Distinct Clinical Syndromes Underlying Acute Mountain Sickness

Abstract: Acute mountain sickness (AMS) is a common problem among visitors at high altitude, and may progress to life-threatening pulmonary and cerebral oedema in a minority of cases. International consensus defines AMS as a constellation of subjective, non-specific symptoms. Specifically, headache, sleep disturbance, fatigue and dizziness are given equal diagnostic weighting. Different pathophysiological mechanisms are now thought to underlie headache and sleep disturbance during acute exposure to high altitude. Hence,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Two independent reports in 2013 provided empirical evidence that sleep disturbance is discordant from other symptoms of AMS (MacInnis et al, 2013;Hall et al, 2014). Hall et al (2014) used network analysis of data from 292 research volunteers exposed to altitudes from 3650 to 5200 m to demonstrate that sleep disturbance correlated poorly with other symptoms of AMS. Importantly, sleep disturbance was absent in 40% of cases with severe headache, long considered a hallmark of AMS.…”
Section: Rationale For Revising the Lake Louise Ams Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Two independent reports in 2013 provided empirical evidence that sleep disturbance is discordant from other symptoms of AMS (MacInnis et al, 2013;Hall et al, 2014). Hall et al (2014) used network analysis of data from 292 research volunteers exposed to altitudes from 3650 to 5200 m to demonstrate that sleep disturbance correlated poorly with other symptoms of AMS. Importantly, sleep disturbance was absent in 40% of cases with severe headache, long considered a hallmark of AMS.…”
Section: Rationale For Revising the Lake Louise Ams Scorementioning
confidence: 99%
“…With 25 years of use in hundreds of publications, the Lake Louise AMS score has provided a robust and practical tool for researchers to diagnose and to score the severity of AMS. Recent opinion (Milledge, 2014) and research (MacInnis et al, 2013;Hall et al, 2014) have suggested that updating the Lake Louise AMS score is in order. This article outlines the brief historical background, reviews diagnostic criteria, describes modifications to the score, and offers suggested experimental procedures that may improve the use of the score in future studies.…”
Section: Introductionmentioning
confidence: 99%
“…This was observational data and collected by the participants and not by direct questioning by a medical officer or on the basis of clinical signs. The validity of the LLS itself has recently been questioned with Hall et al 25 proposing that AMS presents distinct clinical syndromes rather than one entity and that headache is not a feature of all. The LLS was employed as the most widely used score and the score recommended for research purposes 11…”
Section: Discussionmentioning
confidence: 99%
“…This is the fundamental attraction of high-throughput technologies e the probability of measuring important signals is greater if more signals are measured. That such groupings of patients, or disease endotypes, exist is already clear: therapeuticallyimportant sub-classifications have recently been discovered that redefine the clinical syndromes of asthma [30,31], ARDS [32], and acute mountain sickness [33]. In two related autoimmune conditions, ANCA-associated vasculitis (AAV) and systemic lupus erythematosus (SLE), a T-cell gene expression signature clearly delineates two distinct endotypes [34].…”
Section: Treatable Traits and Therapeutically-relevant Subgroupsmentioning
confidence: 99%